Palynological records and n-alkane records of sediment core GeoB10053-7 - Yanming Ruan; Mahyar Mohtadi; Sander van der Kaars; Lydie M Dupont; Dierk Hebbeln; Enno Schefuß (PANGAEA, 2018)
The Maritime Continent, home to widespread tropical rainforest and millions of people, is the primary region of deep atmospheric convection on the Earth. However, debate exists whether the isotopologues of water reflect rainfall amount during the Last Glacial Maximum (LGM), resulting in different interpretations of the LGM climate of the Maritime Continent. Here we present paired leaf wax δ13C and δD records together with pollen data from a sediment core retrieved off East Java dating back to 22,000 years before present. We use three n-alkane homologues (n-C29, n-C31 and n-C33) in order to reconstruct past changes in vegetation types and seasonal rainfall. Our results suggest that in East Java, evergreen rainforest remained the dominant vegetation type in montane regions since the seasonality there remained relatively unaltered over the entire period. In contrast, the East Javanese lowlands were characterised by C4 grass expansion and an extended dry season but a wetter rainy season, thus stronger seasonality, during the LGM.